Tourists' perceptions of memorable experiences: testing the Memorable Tourism Experience scale (MTEs) among tourists to Rovaniemi, Lapland - Sthapit, Erose (fi=Lapin yliopisto|en=University of Lapland|, 2013)
This study investigates the relationship between the eight dimensions of the Memorable Tourism Experience Scale (MTEs) - hedonism, novelty, local culture, refreshment, meaningfulness, involvement, knowledge and adverse feelings and visitor's behavioral intention. Adverse feeling is an addition to the scale. The sample population of this study consists of tourists who have visited Rovaniemi. The sampling frame was obtained by contacting the Rovaniemi Tourist Information Center and local and foreign travel agencies offering trips to Rovaniemi. Facebook was used to approach potential respondents. Primary data was collected using a web-based self-administered questionnaire. A sample of 100 tourists who have visited Rovaniemi completed the questionnaire. The results indicate that two factors of the Memorable Tourism Experience Scale, i.e. local culture and novelty, significantly influences tourists’ behavioral intention to a destination. All the others were not statistically significant. The findings of this present study suggest that tourism activities and on-site experiences should be thoroughly evaluated whether they satisfy the identified memorable tourism experiential components, especially social interaction with local culture and novelty. After evaluating the tourism programs based on the identified memorable tourism experiential dimensions, tourism operators and travel planners in Rovaniemi can design, promote, market and deliver programs that are novel and involve social interaction with local culture, in order to enhance the probability of delivering memorable experiences.